Mechanisms driving variability in the ocean forcing of Pine Island Glacier - Webber, Benjamin G. M.; Heywood, Karen J.; Stevens, David P.; Dutrieux, Pierre; Abrahamsen, E. Povl; Jenkins, Adrian; Jacobs, Stanley S.; Ha, Ho Kyung; Lee, Sang Hoon; Kim, Tae Wan (Nature Communications, 2017)
Pine Island Glacier (PIG) terminates in a rapidly melting ice shelf, and ocean circulation and temperature are implicated in the retreat and growing contribution to sea level rise of PIG and nearby glaciers. However, the variability of the ocean forcing of PIG has been poorly constrained due to a lack of multi-year observations. Here we show, using a unique record close to the Pine Island Ice Shelf (PIIS), that there is considerable oceanic variability at seasonal and interannual timescales, including a pronounced cold period from October 2011 to May 2013. This variability can be largely explained by two processes: cumulative ocean surface heat fluxes and sea ice formation close to PIIS; and interannual reversals in ocean currents and associated heat transport within Pine Island Bay, driven by a combination of local and remote forcing. Local atmospheric forcing therefore plays an important role in driving oceanic variability close to PIIS.